Investigación cualitativa reproducible: un camino que debemos empezar a recorrer - Muñoz Velandía, Oscar Mauricio (Pontificia Universidad Javeriana, 2018)
The movement known as reproducible research (RR) has won space in the quantitative research field as a way to increase the confidence in their results. The RR movement proposes that primary data and computer codes used in the research must be publically available to let other researchers verify published results and to conduct alternative analysis. The advantages related to RR apply well to the qualitative researcher’s work, and will increase the confidence and approval of their results, and additionally could provide advantages like the deeper understanding of their findings, the chance to create investigation networks and groups for collaborative knowledge building. The biggest limitations to produce qualitative reproducible research are ethical considerations associated with making sensitive information openly available. The present article presents some proposals to overcome these difficulties associated with the process of obtaining informed consent and measures to guarantee the confidentiality of data, recognizing that there is much work to be done in this area. Additionally, some steps have been taken to facilitate reproducible qualitative research, including the development of software packages to manage qualitative data, the availability of repositories to make data available and advances developed in reproducible quantitative research implementation.